Características ecofisiológicas, anatômicas e nutricionais de Urochloa spp. Mulato II sob diferentes estruturas de dossel - Assis, Daniel Ferreira de (2018)
The objective was to evaluate the ecophysiological, anatomical and nutritional responses of Urochloa spp. (syn. Brachiaria) Mulato II simulating continuous stocking during periods of water and drought. The treatments were composed of four heights, maintained at 10, 20, 30 and 40 cm. The photosynthetic efficiency was higher in the pastures kept at 20 and 30 cm height, consequently higher levels of soluble carbohydrates were observed in the base of the stem and in the roots, which resulted in a greater accumulation of forage. As for leaf anatomy, it was verified that the heights of 10 and 20 cm had the lowest proportion of lignified tissues, which could have resulted in greater disappearance of the chlorophyll tissue and phloem on the leaf blade. Regarding the CP, NDF, ADF and IVDMD levels, the 10 cm handled grass presented the highest levels of CP, lower levels of NDF and ADF, and higher IVDMD. It was concluded that the pastures of Urochloa spp. (syn. Brachiaria) Mulato II managed at heights between 10 and 30 cm had better morphophysiological, anatomical and qualitative responses.